2013
DOI: 10.1016/j.exger.2012.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Chemical regulation of mid- and late-life longevities in Drosophila

Abstract: We tested the effects of a Class I histone deacetylase inhibitor (HDAcI), sodium butyrate (NaBu), on the longevity of normal- and long-lived strains of Drosophila melanogaster. This HDAcI has mixed effects in the normal-lived Ra strain as it decreases mortality rates and increases longevity when administered in the transition or senescent spans, but decreases longevity when administered over the health span only or over the entire adult lifespan. Mostly deleterious effects are noted when administered by either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 36 publications
(66 reference statements)
1
31
0
Order By: Relevance
“…While these results demonstrating that a reduction of SIN3 leads to reduced longevity are consistent with the locomotor and paraquat sensitivity assays, they are somewhat surprising in light of previously published work indicating that inhibition of HDAC complexes with chemical inhibitors or haplo-insufficiency of Rpd3 leads to increased longevity [49-53]. Possibilities for these differing results will be addressed below.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…While these results demonstrating that a reduction of SIN3 leads to reduced longevity are consistent with the locomotor and paraquat sensitivity assays, they are somewhat surprising in light of previously published work indicating that inhibition of HDAC complexes with chemical inhibitors or haplo-insufficiency of Rpd3 leads to increased longevity [49-53]. Possibilities for these differing results will be addressed below.…”
Section: Resultssupporting
confidence: 75%
“…Rather than reducing lifespan, haploinsufficiency of Rpd3 results in extended longevity [52]. Additionally, alterations in mean lifespan have been observed in flies cultured on various HDAC inhibitors including Trichostatin A (TSA), 4-phenobyturate, suberoylanilide hydroxamic acid (SAHA) and sodium butyrate (NaBu) [49-51, 53]. The amount of drug administered in these studies is important, as high concentrations are lethal.…”
Section: Discussionmentioning
confidence: 99%
“…Third, administration of different HDAC inhibitors like sodium butyrate, TSA, PBA and SAHA result in different changes in mean lifespan. The dosage, time of administration and genetic background of flies used are critical to observing lifespan changes (McDonald et al, 2013). Thus, more work will be required to determine the key epigenetic changes underlying fly lifespan modulation.…”
Section: Nutrient Signaling and Its Effects On The Chromatinmentioning
confidence: 99%
“…The health span is characterized by a tightly regulated gene expression pattern which leads to a maximized tissue function and to a minimized inflammatory and other damage response; the transition phase is characterized by a gradual decline of the cellular regulatory capacity, and the senescent span is characterized by a gradual deregulation of the gene expression pattern (Arking 2009). In a recent study by McDonald et al (2013), a normal-lived Ra strain demonstrated a decreased mortality rate and an increased life span if it was administered with SB during transition or senescent spans, but a decreased life span when administered throughout the entire adult life span or health span only. In a long-lived La strain, however, treatment with SB resulted in mostly deleterious effects on longevity.…”
Section: Sodium Butyratementioning
confidence: 96%
“…In the recent study by McDonald et al (2013), the effects of administration with SAHA throughout Drosophila health span, transition phase, and senescent span have been studied. Treatment with SAHA during the transition or senescent spans resulted in decreased mortality rate and extended longevity compared to the control, while supplementation during the entire adult life span or during the health span only led to decreased longevity in the normal-lived Ra strain.…”
Section: Suberoylanilide Hydroxamic Acid (Saha)mentioning
confidence: 99%